Application of the Exact Regularized Point Particle method (ERPP) to particle laden turbulent shear flows in the two-way coupling regime. (April 2018) - Battista, F.; Gualtieri, P.; Mollicone, J.-P.; Casciola, C.M.
Highlights: The Exact Regularized Point Particle method (ERPP) is used to explore the response of homogeneous shear turbulence in presence of different particle populations. Particles with Kolmogorov Stokes number of order one suppress turbulent kinetic energy when the mass loading is increased. Heavier particles leave this observable almost unchanged with respect to the reference uncoupled case. Turbulence modulation is anisotropic, leaving the streamwise velocity fluctuations less affected by unitary Stokes number particles whilst it is increased by heavier particles. The turbulence modulation occurs throughout the entire range of resolved scales. Small scale anisotropies are enhanced and fluctuations show a greater level of intermittency. Abstract: The Exact Regularized Point Particle method (ERPP), which is a new inter-phase momentum coupling approach, is extensively used for the first time to explore the response of homogeneous shear turbulence in presence of different particle populations. Particle suspensions with different Stokes number and/or mass loading are considered. Particles with Kolmogorov Stokes number of order one suppress turbulent kinetic energy when the mass loading is increased. In contrast, heavier particles leave this observable almost unchanged with respect to the reference uncoupled case. Turbulence modulation is found to be anisotropic, leaving the streamwise velocity fluctuations less affected by unitary Stokes number particles whilst it is increased by heavier particles. The analysis of the energy spectra shows that the turbulence modulation occurs throughout the entire range of resolved scales leading to non-trivial augmentation/depletion of the energy content among the different velocity components at different length-scales. In this regard, the ERPP approach is able to provide convergent statistics up to the smallest dissipative scales of the flow, giving the opportunity to trust the ensuing results. Indeed, a substantial modification of the turbulent fluctuations at the smallest-scales, i.e. at the level of the velocity gradients, is observed due to the particle backreaction. Small scale anisotropies are enhanced and fluctuations show a greater level of intermittency as measured by the probability distribution function of the longitudinal velocity increments and by the corresponding flatness.